Investigasi Potensi Antiviral Ekstrak Biji Kopi Robusta Temanggung Dalam Menghambat Virus Dengue (DENV) - Rizky Ardian Hartanto Sawal; Ayu Ina Solichah; Ismi Puspitasari; Felina Daiman (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) is a significant health issue in tropical and subtropical regions. The discovery of new antiviral agents is crucial due to the lack of effective treatment or vaccines. This study aims to explore the potential of Temanggung robusta coffee bean extract as an anti-DENV agent. The coffee beans were extracted through maceration using 96% ethanol, followed by phytochemical screening to identify active compounds such as alkaloids, flavonoids, saponins, and tannins. Anti-DENV activity and Vero cell cytotoxicity tests were conducted to evaluate the extract's effectiveness and safety. Results indicated that robusta coffee extract exhibited anti-DENV activity with an EC50 of 88.51 µg/ml and a Selectivity Index (SI) of 9.82. The antiviral activity is attributed to bioactive compounds like alkaloids, flavonoids, saponins, and tannins that inhibit DENV replication. Although the extract demonstrated cytotoxicity at high concentrations with CC50 of 869.7 µg/ml, it still holds potential as a therapeutic anti-DENV agent with relatively low toxicity risks. This research opens opportunities for developing robusta coffee-based therapies for DENV infection control in the future.